GENDER CONCEPT: From the Perspective of Nahdlatul Ulama (NU) - Erna Riyanti (Pascasarjana Universitas Wahid hasyim Semarang, 2025)
This study examines the concept of gender from the perspective of Nahdlatul Ulama (NU), the largest religious organization in Indonesia. Through a textual analysis and religious thought approach, this paper explores NU’s views on the roles and relationships between men and women in society and religious life. Nahdlatul Ulama’s perspective is grounded in Islamic teachings, yet also considers Indonesia’s socio-cultural context. The analytical study method is employed to investigate this issue, highlighting NU’s stance on gender-related matters such as family roles, education, and participation in community life. In this context, the paper analyzes how NU responds to contemporary issues regarding women's rights, gender equality, and social changes related to gender roles. The analysis reveals that NU possesses a unique and contextual framework in addressing the concept of gender. While rooted in Islamic values, NU also demonstrates the capacity to adapt religious teachings to social realities. NU’s understanding of gender impacts religious practices and societal values in Indonesia, creating space for discussion and reinterpretation of existing gender norms. This research contributes to understanding the dynamics of gender concepts within the Indonesian religious context, particularly through the lens of Nahdlatul Ulama’s perspectives. The implications of these findings may serve as a foundation for further discussions on how religious organizations can formulate inclusive gender views that positively impact broader society.